Análise de fatores críticos de sucesso na gestão de segurança em atividades de manutenção de linha viva em transmissão em ultra-alta tensão - Leitão, Gerardo Luiz Garcia (2014)
The increasing energy demand in the domestic market in recent decades led the Brazilian government to encourage technical and scientific order that they were defined alternatives to transmission large blocks of power over long distances (more than two thousand kilometers), interconnecting the big huge potential in certain localities watersheds of northern Brazil to the larger consumer centers located in other regions of this country either through specific lines and / or connecting to the national grid. After making various technical feasibility studies based on the existing literature, experiences of other countries and considering the technical and environmental specificities of our country of continental dimensions, the Brazilian government has chosen to introduce the technology of ultra high voltage transmission, which includes the alternating or direct current transmission. In the case of Brazil, it will start with the transmission in Direct Current. The entry in operation here in Brazil of innovative technologies for the transmission of electric energy in ultra high voltage levels brings, beyond traditional technology to industry and society gains technical questions and the general public about risks pertaining to safety and health at work, as well as the community and the surrounding areas. The present work has the objective to identify and analyze the critical success factors in the maintenance of overhead energized transmission lines ( lifeline ) at levels of ultra-high voltage activities (greater than 600 kV in Direct Current and greater than 750 kV in Alternating Current). As for specific goals, relate to the risks and factors referred to how the technological aspects, human resources, safety and logical/laboratory testing support. The methodological approach chosen is, after identification of the relevant theoretical framework at the national and international level, a questionnaire was sent via e-mail from both academia as public and private companies in the Brazilian electric sector and technical analysis in context with the aid of a specific program (search tool). The main findings regarding safety in maintenance tasks on air energized transmission lines ( lifeline ) in extra-high voltages levels and designed for ultra high voltages emphasize the need to maintain tight control of the means of access (scaled and shift) to carry out work to the potential proper and systematic use of individual and collective protective equipment, monitoring of parameters of occupational exposure to electric, magnetic and electromagnetic fields, as well as reconciling design geometry structure (towers) to the collection of experiences field in terms of perceived risk and operational difficulties reported by maintenance crews